Examining the Relationship Between Self-Esteem and Psychological Resilience Levels in Individuals Participating in Summer Sports Schools. - Özcan, Buşra; Arzuoğlu, Kürşat; Şahinler, Yunus (Electronic Turkish Studies)
In this study, it was aimed to examine the relationship between self-esteem and psychological resilience levels in individuals attending summer sports schools. The research universe is Istanbul province. The sample group of the study is composed of a total of 493 volunteer women (238) and men (255) who do athletics, judo, gymnastics and taekwondo sports in summer sports schools in Bakırköy district. While the data was being collected, a personal information form was used to determine the socio-demographic information of the individuals, while the "Adolescent Psychological Resilience Scale" was used to determine their psychological resilience, and the "Rosenberg Self-Esteem Scale" was used to determine their self-esteem. The collected data were analyzed using the SPSS (Statistical Package for Social Sciences) 29.0 package program. Findings: Since the data sets showed normal distribution, frequency and mean values were used. Independent groups t-test, one-way variance analysis and tamhane test for multiple comparisons between different variables, correlation analysis for relationship and recreation analysis for effect were used. As a result, according to the findings obtained as a result of the analyses performed; It was determined that there were negative and positive relationships between psychological resilience and self-esteem of individuals and that adolescent psychological resilience positively and significantly affected self-esteem (p<0.05).